Pengaruh Pemangkasan Cabang dan Penjarangan Bunga Jantan terhadap Pertumbuhan dan Produksi Gherkin dengan Budidaya Hidroponik - Slamet Susanto; Edi Minaji Pribadi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2004)
The objective of the research was to evaluate the effect of branch pruning and male flower thinning on growth and production of gherkin. The research was conducted in a plastic house at Pasir Sarongge Research Station of IPB, Cipanas, from December 1999 to February 2000. A Complete Random Design with two factors was used in this experiment. The first factor was branch pruning consisted of three intensity levels i.e. without branch pruning (CO), a part of branch pruning (CI), and total branch pruning (C2). The second factor was male flower thinning i.e. without thinning (BO), and with thinning (BI). Each treatment was replicated three times. Gherkin variety used in this experiment was SMR 58. The treatments were applied after el1lerging of male flower at 5 weeks after planting, and then it was replicated in every 3 days. Vegetative growth variables observed were length of stem and number of node per plant, while production components observed were number of female flower, number and weight of total fruit, and number and weight of marketable fruit. There was no interaction between branch pruning and male flower thinning treatments on all vegetative and generative variables. Both treatments did not show significant effect on vegetative growth as shown on stem length and node number. At the end of experiment (82 days after planting) the average of stem length was 230.4 - 247.6 cm and node number was 30.2 - 31.0 per plant. The treatments also did not show significant effect on production variable components, except for marketable fruit weight. Number of female flower was 19.0 - 20.3 per plant, while number of fruit was 15.2 - 16.3 per plant. The marketable fruit weight resulted from the total branch pruning treatment was 94% of the total fruit weight, showed significantly higher than that of the control plant (83%). There was a tendency for male flower thinning treatment to result higher marketable fruit as compared with that of the control ones. Key words.. Gherkin, Branch pruning, Male flower thinning, Hydroponics